A new leafhopper genus Discolopeus and nine new species (Hemiptera, Cicadellidae, Deltocephalinae) associated with shrubs, trees and poisonous plants in South Africa - Stiller, Michael (Zootaxa, 2019)
Nine new species in a new genus, Discolopeus gen. n. are described from south-western South Africa, with some species associated with plants that are medicinal or toxic or harmful to ungulates, such as Antizoma miersiana (Menispermaceae), Galenia africana (Aizoaceae), Hyaenanche globosa (Euphorbiaceae) and Zygophyllum foetidum (Zygophyllaceae). New species are as follows: Discolopeus arctus, D. colopeus, D. copeus, D. diacaenus, D. lissus, D. tetracaenus, D. thigmacaenus, D. triacaenus and D. viraktamathi. This new genus is allied to the Bonaspeiini, and distinguished by a paired aedeagal, preatrial process. Cladistic analyses of morphology with parsimony, Bayesian inference and maximum likelihood examined species relationships and showed the monophyly of Discolopeus. Historical biogeographic analyses examined hypotheses of dispersal and vicariance to explain distributions. Niche modelling showed narrow distribution in south-western parts of South Africa.